Regulation of ovarian cancer by protein post-translational modifications - Zhu, Qiugang; Zhou, Huimin; Xie, Feiting (Frontiers in Oncology, 2024)
Ovarian cancer is one of the predominant gynecologic malignancies worldwide, ranking as the fifth leading cause of cancer-induced mortality among women globally. Post-translational modifications (PTMs) refer to the enzyme-catalyzed attachment of functional groups to proteins, thereby inducing structural and functional alterations. Recent evidence suggests that PTMs play multifaceted roles in the pathogenesis of ovarian cancer, influencing processes such as cell cycle, metabolism reprogramming, chemoresistance, and immune responses against cancer. Accordingly, a comprehensive understanding of the diverse PTMs in ovarian cancer is imperative for decoding the complex molecular mechanisms that drive cancer progression. This review discusses the latest developments in the study of protein PTMs in ovarian cancer and introduces pharmacological approaches that target these modifications as therapeutic strategies.